A combined radio-immunotherapy regimen eradicates late-stage tumors in mice - Rakhmilevich, Alexander L.; Tsarovsky, Noah W.; Felder, Mildred; Zaborek, Jen; Moram, Sritha; Erbe, Amy K.; Pieper, Alexander A.; Spiegelman, Dan V.; Cheng, Emily M.; Witt, Cole M.; Overwijk, Willem W.; Morris, Zachary S.; et al. (Frontiers in Immunology, 2024)
Background: The majority of experimental approaches for cancer immunotherapy are tested against relatively small tumors in tumor-bearing mice, because in most cases advanced cancers are resistant to the treatments. In this study, we asked if even late-stage mouse tumors can be eradicated by a rationally designed combined radio-immunotherapy (CRI) regimen. Methods: CRI consisted of local radiotherapy, intratumoral IL-12, slow-release systemic IL-2 and anti- CTLA-4 antibody. Therapeutic effects of CRI against several weakly immunogenic and immunogenic mouse tumors including B78 melanoma, MC38 and CT26 colon carcinomas and 9464D neuroblastoma were evaluated. Immune cell depletion and flow cytometric analysis were performed to determine the mechanisms of the antitumor effects. Results: Tumors with volumes of 2,000 mm3 or larger were eradicated by CRI. Flow analyses of the tumors revealed reduction of T regulatory (Treg) cells and increase of CD8/Treg ratios following CRI. Rapid shrinkage of the treated tumors did not require T cells, whereas T cells were involved in the systemic effect against the distant tumors. Cured mice developed immunological memory. Conclusions: These findings underscore that rationally designed combination immunotherapy regimens can be effective even against large, late-stage tumors.